Development of Human Resources and Competencies to Increase Employee Work Motivation - Zulkifli, Zulkifli; Hakim, Hamka; Patiro, Shine Pintor Siolemba (International Journal of Law Policy and Governance, 2024)
ABSTRACT This research aims to analyze the influence of developing human resources (HR) for Civil Servants (PNS) simultaneously on increasing work motivation at the UPBU Tampa Padang Office, Mamuju Regency. The results of this research show that the development of human resources and employee competency simultaneously has a significant and positive effect on increasing work motivation at the Tampa Padang UPBU Office. This refers to the employee development method that has been applied at Tampa Padang Airport which is considered to be good, because in general the human resource development model seen from research indicators has a clear employee development design. Employees in turn become motivated and gain clarity when it comes to thinking about their career development. Conditions like this are enhanced by the clear direction of employee development through training programs that have been held by Tampa Padang Airport. It is hoped that the recommendations of this research should be in order to create an appropriate employee development strategy model, in order to form qualified and professional employees, aspects such as the vision, mission and goals of the organization should be used as the basis for building employee development patterns. Apart from the dominant aspects mentioned above, there are things that need to be considered, namely discipline, moral and ethical development, then performance assessment, technical training and empowerment.